Multidimensional analysis of anxiety symptoms in patients with chronic obstructive pulmonary disease (COPD) - Li’ao Wang; Dong Miao; Meiying Wang; Gang He; Zhengqiao Li; Yunsheng Hou; Lei Zhang (Scientific Reports)
Abstract To explore the potential classes of anxiety symptoms in patients with chronic obstructive pulmonary disease (COPD) and analyze their distinct characteristics. Convenience sampling was used to select 211 cases of COPD from 12 hospitals in Hebei Province. The following scales were used: General Information Questionnaire, Anxiety Inventory for Respiratory Disease (AIR), BODE index, Montreal Cognitive Assessment (MoCA), and SF-36 Quality of Life scale. Latent profile analysis (LPA) was conducted on the anxiety symptoms of the survey subjects, and univariate analysis and ordinal logistic regression were used to analyze the risk factors of different profiles. Anxiety symptoms among COPD patients were classified into three types: low-risk anxiety type (57.8%), moderate anxiety-fear type (23.2%), and high anxiety-fear type (19.0%). Ordered multinomial logistic regression analysis revealed that the duration of disease, BODE index, MoCA scores, and SF-36 scores were identified as independent risk factors for the potential classes of anxiety symptoms in COPD patients (p < 0.05). There is heterogeneity in anxiety symptoms among COPD patients. Medical staff can provide targeted interventions based on the characteristics and risk factors of different populations to alleviate anxiety symptoms.